First report of rhino-orbital mucormycosis caused by Syncephalastrum racemosum in a diabetic patient with COVID-19 in Iran and review of recent literature - Mojtaba Taghizadeh Armaki; Jalal Jafarzadeh; Saeid Mahdavi Omran; masoumeh Bayani; Ali Tavasoli; Leila Faeli; Mohsen Nosratabadi; Sanaz Yaalimadad; Bahador Nikoueian; Iman Haghani; Maryam Moazeni; Tahereh Shokohi; et al. (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Invasive mucormycosis is a rare mycosis that affects most cases of uncontrolled diabetes and has a high mortality rate. Patients with COVID-19 are at high risk of developing invasive mucormycosis due to the consumption of anti inflammatory drugs such as corticosteroids and dexamethasone. Rhizopus species followed by Rhizomucor spp. and Mucor spp. are the main common etiological agents of rhino-orbital mucormycosis. Therefore, this study aimed to present a case of mucormycosis due to Syncephalastrum racemosum in a diabetic patient with COVID-19 for the first time in Iran.Case report: A 73-year-old diabetic female was referred to Ayatollah Rouhani Hospital in Babol, Iran, with a confirmed COVID-19 diagnosis, based on positive RT-PCR and computed tomography of the lungs. She has received methylprednisolone due to severe lung complications. Nasal involvement and left orbital swelling were observed 20 days after the hospitalization. By sinus endoscopic surgery, debridement was done and histopathology indicated wide hyphae (without septa). The sequenced PCR products displayed Syncephalastrum racemosum. In the antifungal susceptibility test, amphotericin B showed good activity against S. racemosum and the patient survived with timely treatment.Conclusion: This is the first case report of rhino-orbital mucormycosis due to S. racemosum in COVID-19 patient; therefore, S. racemosum can be considered one of the etiological factors of rhino-orbital mucormycosis in COVID-19 cases.